Excluding possible sites of high-energy emission in 3C 84. Issue 4 (13th November 2020) - Linhoff, Lena; Sandrock, Alexander; Kadler, Matthias; Elsässer, Dominik; Rhode, Wolfgang
ABSTRACT: The FR-I galaxy 3C 84, that is identified with the misaligned blazar NGC 1275, is well known as one of the very few radio galaxies emitting gamma-rays in the TeV range. Yet, the gamma-ray emission region cannot be pinpointed and the responsible mechanisms are still unclear. We calculate the optical absorption depth of high-energy photons in the broad-line region of 3C 84 depending on their energy and distance to the central black hole. Based on these calculations, a lower limit on the distance of the emission region from the central black hole can be derived. These lower limits are estimated for two broad-line region geometries (shell and ring) and two states of the source, the low state in 2016 October–December and a flare state in 2017 January. For the shell geometry, we can place the emission region outside the Ly α radius. For the ring geometry and the low flux activity, the minimal distance between the black hole, and the gamma-ray emission region is close to the Ly α radius. In the case of the flaring state (ring geometry), the results are not conclusive. Our results exclude the region near the central black hole as the origin of the gamma-rays detected by Fermi –LAT and Major Atmospheric Gamma-Ray Imaging Cherenkov. With these findings, we can constrain the theoretical models of acceleration mechanisms and compare the possible emission region to the source's morphology resolved by radio images from the Very Long Baseline Array.